Micro and Nano of ZnO Particles Effect on Some Mechanical and Thermal Properties of Epoxy Resin Composites - Ismail Salih Mohammed; Jasim Mohammed Mansoor; Hind W Abdullah (Tikrit Journal of Pure Science, 2021)
Effect of Micro and Nano particle of Zinc Oxide on the mechanical and thermal conductivity properties of an epoxy micro and nanocomposite were studied. Micro and nanocomposites were prepared using Open template method and by different weight ratios of micro and nano of ZnO particles having an average size of (45 µm) and (50 nm), respectively. The mechanical properties of micro and nano-composites were studied using Mechanical measuring devices including tensile strength devices, Shock resistance and Shore hardness Effects of ZnO micro and nanoparticles on the curing behavior of these micro and nanocomposites were investigated utilizing lee disc method. It was found that, ZnO micro and nanoparticles can effectively influence on the mechanical and thermal properties of epoxy coating. In addition, as the results showed an improvement in the mechanical properties of the epoxy compound supported with nanoparticles better than the compound supported with micro-particles, The values of hardness (81,82,82.4,  and 83 N/mm2 ) for the microcomposites and (81.2,82.8,83, and 84 N/mm2) for the nanocomposites compared its value (79) for pure epoxy and the impact values (17.5,18.75,21.25, and 26.25kJ/m2) for the microcomposites and (18,21.25,23.75, and 27.5kJ/m2) for the nanocomposites compared its value (16.25) for pure epoxy and for the ratios (0.1,0.3,0.5, and 0.7 wt%) respectively , while the results showed a decrease in the thermal conductivity of the epoxy compound supported by micro and nanoparticles with an increase in the weight ratios. Micro and Nano particle of ZnO